Synthesis, crystal structure and magnetic properties of [Co(bpcam)2]ClO4·dmso·H2O, [Co(bpcam)2]2[Co(NCS)4]·dmso·H2O and [Ni(bpcam)2]·H2O [Hbpcam = bis(2-pyrimidylcarbonyl)amide]. (22nd June 2017) - Rabelo, Renato; Valdo, Ana K.; Robertson, Craig; Thomas, Jim A.; Stumpf, Humberto O.; Martins, Felipe T.; Pedroso, Emerson F.; Julve, Miguel; Lloret, Francesc; Cangussu, Danielle
Abstract : Synthesis, crystal structures, spectroscopy and magnetic properties of three new bpcam-containing complexes are presented here. Abstract : The preparation, spectroscopic characterization, structural study and magnetic investigation of three new complexes of formula [Co(bpcam)2 ]ClO4 ·dmso·H2 O (1 ), [Co(bpcam)2 ]2 [Co(NCS)4 ]·dmso·H2 O (2 ) and [Ni(bpcam)2 ]·H2 O (3 ) [Hbpcam = bis(2-pyrimidylcarbonyl)amide] are reported. Each bpcam group in1–3 acts as a tridentate ligand being coordinated to the cobalt(iii ) (1 and2 )/nickel(ii ) (3 ) ions through three nitrogen atoms in a mer -arrangement. Six-coordinate cobalt(iii ) and nickel(ii ) occur in1 and3 respectively, whereas six-coordinate cobalt(iii ) and four-coordinate cobalt(ii ) coexist in2 . Cyclic voltammetry of1 in acetonitrile shows the occurrence of one quasi reversible Co III ↔ Co II process. Direct current (dc) variable-temperature magnetic susceptibility measurements on polycrystalline samples of2 and3 were carried out in the temperature range 1.9–295 K. The magnetic behaviour of2 obeys to the zero-field splitting effects ( D Co ) of the 4 A2 ground term of the pseudotetrahedral [Co(NCS)4 ] 2− complex anion. A Curie law for a magnetically isolated nickel(ii ) ion in the high temperatures domain occurs for3, the small decrease of χ M T below 10 K being due zero-field splitting effects. The analysis of the magnetic susceptibility data of2 and3 through the spin Hamiltonian H = D M [ S z 2 − S ( S + 1)/3] + g M βH S [M = Co(2 ) and Ni(3 )] led to the following set of values: g M = 2.37 (2 ) and 2.12 (3 ) and | D M | = 34.7 (2 ) and 1.72 cm −1 (3 ).